Role of regulatory T cells in spinal cord injury - Hao Chen; Hao Peng; Ping-Chuan Wang; Tao Zou; Xin-min Feng; Bo-wen Wan (European Journal of Medical Research, 2023)
Abstract Spinal cord injury is an intricate process involving a series of multi-temporal and multi-component pathological events, among which inflammatory response is the core. Thus, it is crucial to find a way to prevent the damaging effects of the inflammatory response. The research has found that Treg cells can suppress the activation, proliferation, and effector functions of many parenchymal cells by multiple mechanisms. This review discusses how Treg cells regulate the inflammatory cells to promote spinal cord recovery. These parenchymal cells include macrophages/microglia, oligodendrocytes, astrocytes, and others. In addition, we discuss the adverse role of Treg cells, the status of treatment, and the prospects of cell-based therapies after spinal cord injury. In conclusion, this review provides an overview of the regulatory role of Treg cells in spinal cord injury. We hope to offer new insights into the treatment of spinal cord injury.